2017
DOI: 10.1186/s12879-017-2625-0
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and HIV prevalence and associated factors to their co-infection, hepatitis B and hepatitis C viruses prevalence among female sex workers in Rwanda

Abstract: BackgroundHuman Immunodeficiency Virus (HIV), syphilis, Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are sexually transmitted infections (STIs) and share modes of transmission. These infections are generally more prevalent among female sex workers (FSWs).MethodsThis is a cross-sectional study conducted among female sex workers (FSWs) in Rwanda in 2015. Venue-Day-Time (VDT) sampling method was used in recruiting participants. HIV, syphilis, HBV, and HCV testing were performed. Descriptive analyses and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
51
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 26 publications
(32 reference statements)
18
51
10
1
Order By: Relevance
“…Intravenous drug users (IDUs) had a higher prevalence of syphilis, which is consistent with the results from previous studies [17][18][19]. T. pallidum, HIV, HCV and HBV infections share common modes of transmission, leading to co-infections [20,21]. Syphilis could generate genital ulcers and increase the likelihood of HIV virus shedding [21,22].…”
Section: Discussionsupporting
confidence: 87%
“…Intravenous drug users (IDUs) had a higher prevalence of syphilis, which is consistent with the results from previous studies [17][18][19]. T. pallidum, HIV, HCV and HBV infections share common modes of transmission, leading to co-infections [20,21]. Syphilis could generate genital ulcers and increase the likelihood of HIV virus shedding [21,22].…”
Section: Discussionsupporting
confidence: 87%
“…Our finding of an HCV prevalence rate of 1.8% is substantially lower than other surveys conducted in Rwanda, which report HCV prevalence rates of 3.1% in the general population, 4.7% in HIV-infected adults and 9.6% in patients attending Rwanda Military Hospital. 7,21,39,46 However our findings are consistent with the HCV prevalence rates of 1.3% and 1.4% reported in Rwandan health care workers 40 and commercial sex workers, 39 respectively. We conjecture that these variations in HCV infection rates within Rwanda reflect the tendency of HCV to cluster within population subgroups and geographic areas.…”
Section: Discussionsupporting
confidence: 91%
“…Studies from Rwanda report that the prevalence of HBsAg was 2.9% in health care workers 38 and 2.5% in commercial sex workers. 39 Surveys of HIV-infected adults from urban Uganda and Western Kenya report HBsAg prevalence rates of greater than 4%. 40,41 These differences may be explained by the low-risk profile of our study's rural participants, compared to that of population groups known to be at elevated risk of HBV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that syphilis has increased in recent years in the United States and that the number of patients rose from 15.9 to 27.4 per 100.000 population from 2012 to 2016 [26] . There are also studies reporting that HIV-syphilis co-infection rate is as high as 27% among female sex workers [27] .…”
Section: Diagnosis and Laboratory Findingsmentioning
confidence: 99%